The Effect of Oxidative Stress Towards the Expression of Thiamine Biosynthesis Genes (THIC and THI1/THI4) in Oil Palm (Elaeis guineensis) - Zainor Hafisah Che Idris; Aisamuddin Ardi Zainal Abidin; Atiqah Subki; Zetty Norhana Balia Yusof (Tropical Life Sciences Research, 2018)
Thiamine is known to be an important compound in human diet and it is a cofactor required for vital metabolic processes such as acetyl-CoA biosynthesis, amino acid biosynthesis, Krebs and Calvin cycle. Besides that, thiamine has been shown to be involved in plant protection against stress. In this study, the level of expression of THIC and THI1/THI4, the genes for the first two enzymes in the thiamine biosynthesis pathway were observed when oil palm (Elaeis guineensis) was subjected to oxidative stress. Primers were designed based on the consensus sequence of thiamine biosynthesis genes obtained from Arabidopsis thaliana, Zea mays, Oryza sativa, and Alnus glutinosa. Oxidative stress were induced with various concentrations of paraquat and samplings were done at various time points post-stress induction. The expression of THIC and THI1/THI4 genes were observed via RT-PCR and qPCR analysis. The expression of THIC was increased 2-fold, while THI1/THI4 gene transcript was increased 4-fold upon induction of oxidative stress. These findings showed that oil palm responded to oxidative stress by over-expressing the genes involved in thiamine biosynthesis. These findings support the suggestion that thiamine may play an important role in plant protection against stress. Tiamina dikenali sebagai sebatian penting dalam diet manusia dan ia adalah kofaktor yang diperlukan untuk proses metabolisme yang penting seperti biosintesis asetil- CoA, biosintesis asid amino, dan juga kitaran Krebs dan Calvin. Selain itu, tiamina juga telah terbukti terlibat dalam perlindungan tumbuhan terhadap tekanan. Dalam kajian ini, tahap ekspresi transkrip gen THIC dan THI1/THI4, dua enzim pertama dalam tapakjalan biosintesis tiamina telah dianalisa apabila anak pokok kelapa sawit didedahkan kepada tekanan oksidatif. Primer direka berdasarkan perbandingan gen biosintesis tiamina daripada Arabidopsis thaliana, Zea mays, Oryza sativa dan Alnus glutinosa. Tekanan oksidatif telah diberikan melalui parakuat dengan pelbagai kepekatan dan sampel telah diambil di beberapa peringkat masa selepas induksi tekanan. Ekspresi transkrip gen THICdan THI1/THI4 telah dianalisa melalui RT-PCR dan qPCR. Ekspresi transkrip gen THIC telah meningkat sebanyak dua gandaan, manakala ekspresi transkrip gen THI1/THI4 telah meningkat sebanyak empat gandaan selepas induksi tekanan oksidatif diberikan. Penemuan ini menunjukkan bahawa kelapa sawit bertindak balas kepada tekanan oksidatif dengan lebih-meningkatkan ekspresi gen-gen yang terlibat dalam biosintesis thiamine. Penemuan ini menyokong cadangan bahawa tiamina boleh memainkan peranan penting dalam perlindungan tumbuhan terhadap tekanan.